An antibiotic produced by Pseudomonas fluorescens CFBP2392 with antifungal activity against Rhizoctonia solani - Riera, Nadia; Davyt, Danilo; Durán, Rosario; Iraola, Gregorio; Lemanceau, Philippe; Bajsa, Natalia (Frontiers in Microbiology, 2023)
Pseudomonas fluorescens CFBP2392 has been recognized as a potential biocontrol agent due to its ability to suppress damping-off and root rot disease. This isolate has antibacterial activity in vitro as many other strains from the Pseudomonas fluorescens complex., this isolate has antibacterial activity in vitro. In this work, the antibacterial and antifungal activity of the strain were explored. Dual culture assays evidenced the antifungal activity of the strain against different phytopathogens: Alternaria sp, Pythium ultimun, Fusarium oxysporum and Rhizoctonia solani. Purification of the growth media with chemical extraction and HPLC identified an antifungal compound that altered R. solani growth and ultrastructure Purification of an antifungal fraction was performed by preparative HPLC from the chemical extraction of growth media. The fraction showed altered R. solani growth and ultrastructure. Transmission electron microscopy revealed the purified compound produced induced hypertrophied mitochondria, membranous vesicles and a higher number of vacuoles in R. salani cytoplasm. In addition, co-cultivation of P. fluorescens CFBP2392 with R. solani resulted in an enlarged and deformed cell wall. To gain genomic insights on this inhibition, the complete genome of P. fluorescens CFBP2392 was obtained with Oxford Nanopore technology. Different biosynthetic gene clusters (BGCs) involved in specialized metabolites production including a lokisin-like and a koreenceine-like cluster were identified. In accordance with the putative BGCs identified, sequence phylogeny analysis of the MacB transporter in the lokisin-like cluster further supports the similarity with other transporters from the amphisin family. Our results give insights into the cellular effects of the purified microbial metabolite in R. solani ultrastructure and provide a genomic background to further explore the specialized metabolite potential.